2020
DOI: 10.1038/s41598-020-78986-9
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic masks the way people perceive faces

Abstract: The unprecedented efforts to minimize the effects of the COVID-19 pandemic introduce a new arena for human face recognition in which faces are partially occluded with masks. Here, we tested the extent to which face masks change the way faces are perceived. To this end, we evaluated face processing abilities for masked and unmasked faces in a large online sample of adult observers (n = 496) using an adapted version of the Cambridge Face Memory Test, a validated measure of face perception abilities in humans. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
182
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(209 citation statements)
references
References 44 publications
26
182
0
1
Order By: Relevance
“…Further, other pandemic-related factors which are likely to contribute to the appraisal of social scenes should be assessed. For instance, the use of face masks, which has already been found to contribute to changes in other social cognitive processes, like face perception (Freud et al, 2020), the ability to recognize emotions (Carbon, 2020) and the attribution of trust (Marini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Further, other pandemic-related factors which are likely to contribute to the appraisal of social scenes should be assessed. For instance, the use of face masks, which has already been found to contribute to changes in other social cognitive processes, like face perception (Freud et al, 2020), the ability to recognize emotions (Carbon, 2020) and the attribution of trust (Marini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…3]. In addition, they are assumed to increase mental stress during interpersonal encounters; they might make social judgements more difficult by partially hiding facial features indicating another person's emotions and intentions, thereby hampering smooth social interactions [5][6][7]. Some authors have already suggested how to deal with these social issues, for example by designing face masks with simple expressive display elements [8] or inducing facial muscle paralysis by botulinum toxin targeting the muscles of the top visible half of the face in order to reduce negative emotions and promote well-being for both the mask-wearer and those who come in contact with that individual [9].…”
Section: Introductionmentioning
confidence: 99%
“…First studies have revealed that the identification of an individual [ 6 , 7 ] and the recognition of an emotional state are faultier for faces covered by MNCs [ 5 , 10 , 20 ]. In a sample of 40 healthy participants, recognising basic emotions such as happiness, anger, fearfulness, and disgust was less accurate when faces were covered by MNCs, and participants often misclassified disgusted faces as angry, and joyful faces as neutral, that is, as displaying no emotion at all [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…More generally, facial and social skills are essential abilities for navigating in our modern society. With the ongoing pandemic, the ability to decode social information from faces on a screen or from the eye region (as faces are partially occluded with masks) has recently become one of the main tools in social interactions 91 . This ability relies on a complex cerebral network 28 .…”
Section: What Are the Interventional Implications Of These Results?mentioning
confidence: 99%